Objectives, Thrusts and Macro-Dimensions of the Eighth Plan - Planning Commission (Planning Commission, 1991)
The Eighth Five Year Plan is being launched against the backdrop of momentous changes taking place in the world. The end of the cold war, the transformations in Eastern Europe and the Soviet Union and the imminent emergence of a common market in Western Europe are events of truly historic significance. These changes will have a profound impact on both the structure of international relations and the world economy. Simultaneously, most developing countries have embarked on bold measures of reform in restructuring their economies and opening up to forces of competition, both domestic and foreign. The wave of economic reforms that is sweeping the developing world and the hitherto centrally planned economies has important implications for India in the 90’s.
Planning Commission New Delhi